Pengaruh Kepemimpinan, Budaya Organisasi, Lingkungan Kerja Terhadap Kepuasan Kerja dan Kinerja Pegawai Pada Badan Kepegawaian dan Pengembangan Sumber Daya Manusia (BKPSDM) Kabupaten Bulungan Kalimantan Utara - Totok Radiatmoko; Ana Sriekaningsih; Elizabeth Novi Kusumaningrum (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
The aim of the research is to determine the influence of leadership, organizational culture, work environment both directly and indirectly on the performance of employees of the Bulungan Regency Personnel and Human Resources Development Agency (BKPSDM) after job satisfaction. This type of quantitative research is explanatory descriptive. The total population and sample is 64 people. Data were collected by distributing questionnaires and continued with analysis using path analysis. The results of hypothesis testing proved that leadership shows a positive and insignificant influence on job satisfaction. Organizational culture shows a positive and insignificant influence on job satisfaction. The work environment shows a positive and significant influence on job satisfaction. Leadership directly has a positive and insignificant effect on employee performance, meaning that every increase in leadership will increase employee performance in carrying out the tasks for which they are responsible, but the increase is relatively small. Organizational culture has a direct, positive and insignificant effect on employee performance. Directly, work environment variables have a positive and significant effect on employee performance. This shows that if the work environment is improved by one unit, it will directly increase employee performance. Job satisfaction has a significant effect on employee performance. The direct influence between leadership, organizational culture and work environment both partially and simultaneously on performance is greater than indirect after going through job satisfaction so that the direct influence is more dominant than the indirect influence.